The assessment of early parenting orientation - Evans, Janet (Department of Sociology, 2016)
This study focuses on parenting styles as adopted by men and women during pregnancy and early parenthood. Parenting style is examined following the categories outlined by Raphael-Left's model (1983, 1985b, 1991 ). The sample consisted of 57 women and 39 men. Mailed, self administered questionnaires were used with all participants. The psychometric properties of the questionnaires devised by Raphael-Left (1983, 1985b, 1991) are examined. The study also assesses the stability of these orientations from the beginning of pregnancy into early parenthood. The results of the psychometric evaluation reveal that the questionnaires are not internally consistent. Further, a model consisting of a continuum of parenting style is not supported. The stability of parental orientation over time was not established, parenting style appears to change particularly after childbirth.